A kind of polyurethane thermal conductive structural adhesive
By adding organic alkali and organic acid to the components A and B of the polyurethane structural glue, modified inorganic fillers, respectively, to adjust the acid-base neutralization reaction, the problem of polyurethane structural glue is solved, and excellent bonding and thermal conductivity and a long opening time are achieved.
Patent Information
- Application Number
- CN202411405476.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The two-component polyurethane structural adhesive is sensitive to moisture during storage and curing, resulting in deterioration, deterioration of adhesive properties and crust, which in turn affects the service life of the power battery.
By adding alkaline organic alkali-coated and modified inorganic filler and acidic organic acid-coated inorganic filler to components A and B, the acid-base neutralization reaction of structural glue is adjusted, the opening time is extended and the crust phenomenon is avoided.
The excellent bonding performance, good thermal conductivity and long opening time of polyurethane thermally conductive structural adhesive are achieved, and deterioration and crust problems caused by moisture sensitivity are avoided.
Smart Images

Figure BDA0005077002620000041 
Figure BDA0005077002620000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives and relates to a polyurethane heat-conducting structural adhesive. Background Art
[0002] With the rapid development of new energy vehicles, the demand for power batteries is also increasing, and the demand for power battery adhesives is also growing rapidly. Polyurethane structural adhesives have the advantages of long storage cycle, adjustable modulus, safety and environmental protection, and have been widely used in the bonding field of power batteries. However, during the storage and curing process, the two-component polyurethane structural adhesive is extremely sensitive to moisture. When the production line is stopped for a long time or the container storing the structural adhesive has poor sealing, the component containing polyisocyanate is easy to react with moisture in the air, which not only causes the structural adhesive to deteriorate and the bonding performance to deteriorate, but also causes crusting, resulting in blockage of the mixing hose.
[0003] In summary, how to effectively extend the open time of the polyurethane thermal conductive structural adhesive while ensuring that it has good thermal conductivity and bonding properties is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0004] In view of the defects existing in the prior art, the present invention provides a polyurethane thermally conductive structural adhesive. By adding an alkaline organic base-coated modified inorganic filler and an acidic organic acid-coated modified inorganic filler into component A and component B, respectively, the structural adhesive has excellent bonding properties, good thermal conductivity and a long open time.
[0005] The present invention provides a polyurethane heat-conducting structural adhesive, comprising a component A and a component B in a volume ratio of (0.9-1.1):1;
[0006] The component A comprises, by weight percentage, 15 wt% to 35 wt% of castor oil, 5 wt% to 14 wt% of a first polyester polyol, 2 wt% to 5 wt% of a chain extender, 0.5 wt% to 2.5 wt% of a coupling agent, 0.02 wt% to 0.08 wt% of a catalyst, 50 wt% to 70 wt% of a first modified inorganic filler, 5 wt% to 8 wt% of a molecular sieve, and 0.5 wt% to 2.5 wt% of hydrophobic silica;
[0007] The B component includes, by weight percentage, 5wt% to 15wt% of terminal isocyanate polyurethane prepolymer, 5wt% to 15wt% of isocyanate, 50wt% to 70wt% of second modified inorganic filler, 0.5wt% to 2.5wt% of dewatering agent, 0.3wt% to 1.5wt% of hydrophobic silica, and 0 to 3.5wt% of plasticizer;
[0008] The first modified inorganic filler includes a first inorganic filler and a first modified layer coated on the surface of the first inorganic filler, and the first modified layer includes an organic base;
[0009] The second modified inorganic filler includes a second inorganic filler and a second modified layer coated on the surface of the second inorganic filler, and the second modified layer includes an organic acid.
[0010] The polyurethane thermal conductive structural adhesive as described above, wherein the isocyanate-terminated polyurethane prepolymer is obtained by reacting a second polyester polyol and an isocyanate in a mass ratio of (20-50): (50-80);
[0011] Preferably, the second polyester polyol is obtained by polymerizing a diol and a dicarboxylic acid; the molecular weight of the second polyester polyol is 500 to 3500 Da, and the hydroxyl value is 30 to 224 mgKOH / g.
[0012] The polyurethane thermal conductive structural adhesive as described above, wherein the diol is selected from branched diols, preferably one or more of methyl propanediol, methyl pentanediol, and dihydrochloric acid, and more preferably dihydrochloric acid.
[0013] The polyurethane thermal conductive structural adhesive as described above, wherein the diol is selected from dimethoate, and the molecular weight of the second polyester polyol is 2800-3200 Da, and the hydroxyl value is 32-40 mgKOH / g.
[0014] The polyurethane thermal conductive structural adhesive as described above, wherein the organic acid has a pKa value of 2 to 5, a boiling point of >100°C, and a solubility of >0.1 g / 100 g water;
[0015] And / or, the organic base has a pKb value of 0.5 to 4 and a solubility of >0.1 g / 100 g water.
[0016] The polyurethane thermal conductive structural adhesive as described above, wherein the organic acid is selected from one or more of pyruvic acid, barbituric acid, and lactic acid;
[0017] And / or, the organic base is selected from 1,8-diazabicycloundec-7-ene.
[0018] The polyurethane thermally conductive structural adhesive as described above, wherein the first inorganic filler and the second inorganic filler are each independently selected from one or more of aluminum oxide, aluminum hydroxide, and magnesium oxide.
[0019] The polyurethane thermal conductive structural adhesive as described above, wherein the first modified inorganic filler is prepared by a method comprising the following steps: dispersing the first inorganic filler in deionized water, adding the organic base thereto to obtain a first dispersion with a solid content of 40% to 60%, adding a first silane coupling agent to the first dispersion, reacting at 60 to 80° C. for 30 min to 60 min to obtain the first modified inorganic filler; the amount of the organic base added is 100 to 1000 ppm of the mass of the deionized water in the first dispersion, preferably 200 to 500 ppm;
[0020] And / or, the second modified inorganic filler is prepared by a method comprising the following steps: dispersing the second inorganic filler in deionized water, adding the organic acid thereto to obtain a second dispersion with a solid content of 40% to 60%, adding a second silane coupling agent to the second dispersion, reacting at 60 to 80° C. for 30 min to 60 min to obtain the second modified inorganic filler; the amount of the organic acid added is 0.1 to 10 ppm of the mass of the deionized water in the second dispersion, preferably 0.5 to 2.5 ppm.
[0021] In the polyurethane thermal conductive structural adhesive as described above, the first silane coupling agent and the second silane coupling agent are each independently selected from one or more of dodecyltriethoxysilane, octadecyltriethoxysilane coupling agent, and hexadecyltriethoxysilane coupling agent.
[0022] The polyurethane thermal conductive structural adhesive as described above, wherein the chain extender is selected from one or more of dipropylene glycol, diethylene glycol, and 1,2-propylene glycol;
[0023] And / or, the dewatering agent is selected from one or more of toluenesulfonyl isocyanate and triethyl orthoformate;
[0024] And / or, the isocyanate is selected from one or more of 4,4'-dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, polymethylene polyphenyl polyisocyanate;
[0025] And / or, the catalyst is selected from one or more of aliphatic amine catalysts and organic metal catalysts.
[0026] The implementation of the present invention has at least the following beneficial effects:
[0027] The polyurethane heat-conductive structural adhesive provided by the present invention is a two-component heat-conductive structural adhesive having component A and component B, wherein the organic acid in the modified layer coated on the surface of the second modified inorganic filler in component B can react with the byproduct primary amine compound generated by the reaction of isocyanate with water, thereby increasing the open time of component B and avoiding the skinning phenomenon. After component A and component B are mixed, the organic base in the modified layer coated on the surface of the first modified inorganic filler in component A can react with the unreacted organic acid in component B to undergo an acid-base neutralization reaction so that the structural adhesive as a whole presents an intermediate or weak alkalinity, thereby avoiding corrosion to the bonding substrate and ensuring that the structural adhesive has good bonding performance. At the same time, the inorganic filler matrix has good thermal conductivity, which can make the structural adhesive have a higher thermal conductivity coefficient. In summary, the polyurethane heat-conductive structural adhesive of the present invention has the advantages of good bonding performance, good thermal conductivity and long open time. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The present invention provides a polyurethane heat-conducting structural adhesive, comprising a component A and a component B in a volume ratio of (0.9-1.1):1;
[0030] Component A includes, by weight percentage, 15 wt% to 35 wt% of castor oil, 5 wt% to 14 wt% of the first polyester polyol, 2 wt% to 5 wt% of a chain extender, 0.5 wt% to 2.5 wt% of a coupling agent, 0.02 wt% to 0.08 wt% of a catalyst, 50 wt% to 70 wt% of a first modified inorganic filler, 5 wt% to 8 wt% of a molecular sieve, and 0.5 wt% to 2.5 wt% of hydrophobic silica;
[0031] Component B includes, by weight percentage: 5wt% to 15wt% of terminal isocyanate polyurethane prepolymer, 5wt% to 15wt% of isocyanate, 50wt% to 70wt% of second modified inorganic filler, 0.5wt% to 2.5wt% of dewatering agent, 0.3wt% to 1.5wt% of hydrophobic silica, and 0 to 3.5wt% of plasticizer;
[0032] Wherein, the first modified inorganic filler comprises a first inorganic filler and a first modified layer coated on the surface of the first inorganic filler, and the first modified layer comprises an organic base;
[0033] The second modified inorganic filler includes a second inorganic filler and a second modified layer coated on the surface of the second inorganic filler, and the second modified layer includes an organic acid.
[0034] When component B comes into contact with air, the isocyanate group at the end of the prepolymer or the single isocyanate component will react with the moisture in the air to form a carbamic acid intermediate, which will then decompose to form primary amine compounds and carbon dioxide gas. The reaction equation is as follows:
[0035]
[0036] If the generated primary amine compounds are not removed in time, they will react with isocyanate to generate urea compounds, resulting in the appearance of skinning. The reaction equation is as follows:
[0037] RN=C=O+RNH2→RNHCONHR.
[0038] The present invention adds a second modified inorganic filler to component B. On the one hand, the filler itself has heat-conducting and flame-retardant functions. On the other hand, the organic acid in the surface modified layer of the filler, as an organic component, can improve the compatibility of the filler of the inorganic component with the organic components such as the terminal isocyanate polyurethane prepolymer and isocyanate in component B. As an acidic component, it can react with the primary amine compound generated by the reaction of isocyanate with water to produce an acid-base neutralization reaction, thereby avoiding the reaction of the primary amine compound with isocyanate to generate a urea compound, and further avoiding the occurrence of skinning, thereby extending the open time of component B and effectively reducing the risk of clogging the pipeline due to a long-term stoppage of the production line.
[0039] However, the organic acid component coated on the surface of the second modified inorganic filler makes it have a certain acidity, and when applied to the bonding substrate, it will corrode the substrate, thereby affecting the bonding performance of the structural adhesive. Based on this consideration, the present invention adds a first modified inorganic filler to component A, wherein the organic base component coated on the surface of the first modified inorganic filler can react with the organic acid component coated on the surface of the second modified inorganic filler when the two components A and B are mixed, so that the two components A and B are neutral or weakly alkaline after mixing, thereby preventing the thermal conductive structural adhesive from corroding the bonding substrate.
[0040] In summary, the two-component polyurethane thermally conductive structural adhesive provided by the present invention has excellent bonding performance and thermal conductivity, and also has the advantage of a long open time.
[0041] In some specific embodiments, the isocyanate-terminated polyurethane prepolymer in component B is obtained by reacting the second polyester polyol and isocyanate in a mass ratio of (20-50): (50-80). Within the above mass ratio range, it is beneficial to adjust the prepolymer to have a suitable NCO value, thereby obtaining better cross-linking properties to improve the bonding properties of the thermally conductive structural adhesive.
[0042] The present invention does not impose any particular limitation on the isocyanate used in the above reaction, and the isocyanate may be selected from one or more of 4,4'-dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, polymethylene polyphenyl polyisocyanate.
[0043] In some specific embodiments, the preparation of the prepolymer comprises the following steps:
[0044] The second polyester polyol is heated to 110-150°C, vacuumed, stirred and dehydrated for 2 hours, cooled to 60-65°C, and then isocyanate is added, and then the temperature is raised to 80°C, reacted for 2-2.5 hours, and then cooled to room temperature to prepare a terminal isocyanate polyurethane prepolymer.
[0045] In the present invention, the first polyester polyol and the second polyester polyol may be of the same or different types. Preferably, the second polyester polyol is selected from polyester polyols having good hydrophobic properties to improve the hydrophobic properties of component B and further extend the open time of component B.
[0046] In some specific embodiments, the second polyester polyol used in the above reaction is obtained by polymerizing a diol with a dicarboxylic acid;
[0047] The molecular weight of the second polyester polyol is 500-3500 Da, and the hydroxyl value is 30-224 mgKOH / g.
[0048] The larger the molecular weight, the longer the molecular chain of the polyester polyol, and a longer molecular chain is beneficial to improving the hydrophobicity of the prepolymer; the hydroxyl value represents the hydroxyl content in the molecule. The hydroxyl group is a hydrophilic group. The higher its content, the stronger the hydrophilicity of the molecular chain. Within the above molecular weight and hydroxyl value range, polyester polyol has both a higher molecular weight and a lower hydroxyl group, which can improve the hydrophobicity of the terminal isocyanate polyurethane prepolymer, inhibit its reaction with moisture in the air, and further extend the open time of component B.
[0049] In the present invention, the molecular weight and hydroxyl value of the polyester polyol are obtained by testing with reference to GB / T 7383-2020.
[0050] In some specific embodiments, the diol is selected from branched diols. Branched diols refer to a diol having two hydroxyl groups as the main chain, and other branches are connected to the main chain. The branched structure is beneficial to improving the hydrophobicity of the second polyester polyol, thereby improving the hydrophobicity of the prepolymer.
[0051] Preferably, the diol is selected from one or more of methyl propanediol, methyl pentanediol and dihydrochloric acid. In addition to two hydroxyl groups, the above diols have more carbon side chains in the main body of the molecule, and the presence of carbon side chains can further improve the hydrophobicity of the prepolymer.
[0052] More preferably, the diol is selected from chlorpyrifos, and the molecular weight of the second polyester polyol is 2800-3200Da, and the hydroxyl value is 32-40mgKOH / g. The inventors have found that the carbon side chains in chlorpyrifos can be coated on the surface of the prepolymer to form an additional hydrophobic layer, and by adjusting the molecular weight and hydroxyl value of the second polyester polyol within the above range, the prepolymer can be in a more ideal hydrophobic state, so that the open time of component B is further extended. In addition, a higher molecular weight within the above range will make the second polyester polyol have a lower hydroxyl value, and thus make the prepolymer have a lower crosslinking density, which is beneficial for the prepolymer to obtain a lower viscosity, and thus is beneficial for the thermal conductive structural adhesive to have good filling and coating properties.
[0053] In a specific embodiment, the dicarboxylic acid used in the above polymerization process includes but is not limited to one or more of azelaic acid and adipic acid.
[0054] In some preferred embodiments, the pKa value of the organic acid is 2 to 5, the boiling point is greater than 100°C, and the solubility is greater than 0.1g / 100g water. The pKa value of the organic acid is within the above range to avoid corrosion of the substrate by excessive acidity. At the same time, limiting its boiling point to greater than 100°C can avoid the volatilization of the organic acid as the water is dried during the modification stage. At the same time, limiting its solubility to greater than 0.1g / 100g water can ensure that it has good compatibility with water, which is conducive to modification on the surface of the inorganic filler. Exemplary organic acids that meet the above requirements include propionic acid, glyceric acid, gluconic acid, pyruvic acid, barbituric acid, lactic acid, etc.
[0055] In some preferred embodiments, the pKb value of the organic base is 0.5 to 4, and the solubility is greater than 0.1 g / 100 g of water. Within the above pKb value range, the organic base has suitable alkalinity and solubility, which is beneficial for neutralizing the excess organic acid after the A and B components are mixed, and its good water solubility is also beneficial for modifying the surface of the inorganic filler. Exemplary organic bases that meet the above requirements include triethylamine, cyclohexylamine, p-aminophenol, 1,8-diazabicycloundec-7-ene (DBU), etc.
[0056] In some more preferred ways, the organic acid in the second modified layer is selected from one or more of pyruvic acid, barbituric acid, and lactic acid. The pKa values of the above three acids are 2.49, 4.01, and 4.01, respectively. They all have suitable acidity, are not easy to corrode the substrate during the bonding process, and have a high boiling point, and are not easy to volatilize during the modification process. Among them, the boiling point of pyruvic acid is 165°C, which is miscible with water. During the modification process, it can be dissolved in water, which will make the modification of the inorganic filler more uniform and stable; the boiling point of barbituric acid is 260°C, but its state is solid and slightly soluble in water. Even if it has a high boiling point, its compatibility with water is poor, which will affect the uniformity of the modified filler; lactic acid has good compatibility with water, but its boiling point is relatively low, which is 122°C. It is easy to dry and volatilize with water in the subsequent drying stage, thereby affecting the open time of the polyurethane thermal conductive structural adhesive. Therefore, more preferably, the organic acid in the second modified layer is selected from pyruvic acid.
[0057] In some more preferred embodiments, the organic base in the first modified layer is selected from 1,8-diazabicycloundec-7-ene (DBU). DBU has alkaline properties and hydrogen bond forming ability, and can accept protons to form ion pairs for reaction. At the same time, compared with other types of organic bases, DBU has large steric hindrance, weak nucleophilicity, is not easy to react with isocyanate, and has good structural stability.
[0058] The present invention does not specifically limit the types of the first inorganic filler and the second inorganic filler, which can be selected from inorganic fillers with thermal conductivity commonly used in the art, specifically including but not limited to one or more of aluminum oxide, aluminum hydroxide, and magnesium oxide.
[0059] In a specific embodiment, the first modified inorganic filler is prepared by a method comprising the following steps: dispersing the first inorganic filler in deionized water, adding an organic base thereto to obtain a first dispersion with a solid content of 40% to 60%, adding a first silane coupling agent to the first dispersion, reacting at 60 to 80° C. for 30 min to 60 min to obtain a first modified inorganic filler; the amount of the organic base added is 100 to 1000 ppm of the mass of the deionized water in the first dispersion, preferably 200 to 500 ppm.
[0060] In a specific embodiment, the second modified inorganic filler is prepared by a method comprising the following steps: dispersing the second inorganic filler in deionized water, adding an organic acid thereto to obtain a second dispersion with a solid content of 40% to 60%, adding a second silane coupling agent to the second dispersion, reacting at 60 to 80° C. for 30 min to 60 min to obtain a second modified inorganic filler; the amount of organic acid added is 0.1 to 10 ppm of the mass of deionized water in the second dispersion, preferably 0.5 to 2.5 ppm.
[0061] Controlling the addition amount of the organic base and the organic acid within the above range is conducive to the organic base and the organic acid forming a good coating on the surface of the first inorganic filler and the second inorganic filler, respectively.
[0062] Furthermore, during the preparation of the first modified inorganic filler, the mass of the first silane coupling agent added is 1% to 5% of the mass of the first inorganic filler; and / or, during the preparation of the second modified inorganic filler, the mass of the second silane coupling agent added is 1% to 5% of the mass of the second inorganic filler.
[0063] Furthermore, in order to fully carry out the first modification and the second modification, the reactions can be carried out under stirring, and the stirring speed can be controlled to be 800-1500 r / min.
[0064] After the first modification and the second modification are completed, the reaction system is further subjected to solid-liquid separation and drying. The present invention does not limit the method of solid-liquid separation, for example, it can be centrifugation, filtration, etc. The drying process can be carried out in a blast drying oven, and the drying time can be determined according to the moisture content on the surface of the product.
[0065] In the preparation process of the first modified inorganic filler and the second modified inorganic filler, respectively adding the first silane coupling agent and the second silane coupling agent can adjust the surface polarity of the first inorganic filler and the second inorganic filler, which is conducive to adsorbing the organic base on the surface of the first inorganic filler and the organic acid on the surface of the second inorganic filler, so as to better complete the coating process. In some preferred embodiments, the silane coupling agent is selected from one or more of dodecyl triethoxysilane, octadecyl triethoxysilane coupling agent, and hexadecyl triethoxysilane coupling agent, and more preferably octadecyl triethoxysilane coupling agent. Compared with other types of silane coupling agents, the hydrophobic performance of octadecyl triethoxysilane coupling agent is higher.
[0066] The present invention does not specifically limit the type of the chain extender in component A, which can be selected from chain extenders conventionally used in the art, including but not limited to one or more of dipropylene glycol, diethylene glycol, and 1,2-propylene glycol.
[0067] In some specific embodiments, the water scavenger in component B is selected from one or more of toluenesulfonyl isocyanate and triethyl orthoformate.
[0068] In some specific embodiments, the isocyanate in component B is selected from one or more of 4,4'-dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), and polymethylene polyphenyl polyisocyanate. The present invention does not impose any special restrictions on the sources of the above isocyanates, and conventional commercial products in the art can be selected, such as Wanhua's MDI-100L, PM200, and Kumho Mitsui's liquefied MDI.
[0069] The present invention does not specifically limit the type of catalyst in component A, and it can be selected from conventional catalysts in the art that can be used to catalyze the polymerization reaction of the isocyanate-terminated polyurethane prepolymer in component B with isocyanate and the polyester polyol in component A to generate polyurethane, and can be aliphatic amine catalysts and / or organic metal catalysts. Specifically, the organic metal catalyst can be an organic tin catalyst T12 or the like.
[0070] The first polyester polyol in the A component is preferably a bisphenol A-modified polyester polyol.
[0071] The coupling agent in component A can improve the mechanical properties and processing properties of the polyurethane thermal conductive structural adhesive. The present invention does not specifically limit its type, and it can be selected from the types of coupling agents commonly used in the art, such as one or more of KH-550, KH-560, and KH-570.
[0072] The plasticizer in component B can adjust the viscosity and strength of the system. The present invention does not specifically limit its type, and it can be selected from the types of plasticizers commonly used in the art, including but not limited to one or more of BDP, DPHP, and DINP.
[0073] In some specific embodiments, the polyurethane thermal conductive structural adhesive of the present invention is prepared by a method comprising the following steps:
[0074] 1) Preparation of component A: Castor oil, a first polyester polyol, a chain extender, a coupling agent, a catalyst, a catalyst, a first modified inorganic filler, a molecular sieve, and hydrophobic silica are mixed in a specific mass ratio, stirred evenly, and vacuumed to obtain component A;
[0075] 2) Preparation of component B: The isocyanate-terminated polyurethane prepolymer, isocyanate, the second modified inorganic filler, the water scavenger, the hydrophobic silica and the plasticizer are mixed in a specific mass ratio, stirred evenly and vacuumed to obtain component B.
[0076] 3) Component A and component B are mixed in a volume ratio of (0.9-1.1):1 to obtain a polyurethane thermal conductive structural adhesive.
[0077] The polyurethane thermal conductive structural adhesive provided by the present invention will be introduced in detail below in conjunction with specific embodiments.
[0078] In the following examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods. Experimental methods without specific conditions are selected according to conventional methods and conditions in the art or according to the product instructions.
[0079] Example 1
[0080] This embodiment provides a polyurethane thermal conductive structural adhesive, which includes a component A and a component B in a volume ratio of 1:1. The preparation method of the thermal conductive structural adhesive includes the following steps:
[0081] 1) Preparation of DBU-modified aluminum hydroxide filler: weigh aluminum hydroxide raw material and put it in a beaker, add an appropriate amount of deionized water, add 300ppm of DBU based on the mass content of deionized water, so that the system reaches a liquid-solid ratio of 1:1 by mass, and then weigh 3% of octadecyltriethoxysilane based on the mass of aluminum hydroxide raw material and add it to the reaction system. At 80°C and a speed of 1000r / min, the modification is carried out for 40 minutes to complete the modification process. The modified product is filtered and placed in an electric blast drying oven for drying. After 8 hours, it is taken out to obtain a dry DBU-modified aluminum hydroxide filler.
[0082] 2) Preparation of pyruvic acid-modified aluminum hydroxide filler: weigh aluminum hydroxide raw material and put it in a beaker, add an appropriate amount of deionized water, add 0.8ppm of pyruvic acid based on the mass content of deionized water, so that the system reaches a liquid-solid ratio of 1:1 by mass, and then weigh 3% octadecyltriethoxysilane and add it to the reaction system. At 80°C and a speed of 1000r / min, the modification is carried out for 40 minutes to complete the modification process. The modified product is filtered and placed in an electric blast drying oven for drying. After 8 hours, it is taken out to obtain a dry pyruvic acid-modified aluminum hydroxide filler.
[0083] 3) Preparation of terminal isocyanate polyurethane prepolymer: Adipic acid and repellent alcohol were mixed at a mass ratio of 1000:1010 and added to a four-necked flask at room temperature, and nitrogen was passed through for protection and condensation reflux. The mixture was heated from room temperature to 80°C to partially melt the material, and then stirring was started and the temperature was raised to 145°C for esterification reaction, and the temperature was kept for 8 hours. Then the temperature was raised to 200°C at a rate of 10°C / min for polycondensation reaction, and the temperature was kept for 2 hours. Add phthalate accounting for 0.1% of the total mass of adipic acid and repellent alcohol, continue to keep warm and react for 4 hours, and obtain a polyester polyol derived from repellent alcohol with a molecular weight of 2900-3000Da and a hydroxyl value of 38-40mgKOH / g; heat 500g of the prepared polyester polyol derived from repellent alcohol to 110°C, evacuate, stir and dehydrate for 2 hours, cool to 60-65°C, add an equal amount of liquefied MDI, then heat to 80°C, react for 2 hours, and then cool to room temperature to prepare a terminal isocyanate polyurethane prepolymer.
[0084] 4) Preparation of component A: 17 wt% of castor oil, 9 wt% of ethoxylated bisphenol A modified polyester polyol, 2.5 wt% of 1,4-butanediol, 0.5 wt% of coupling agent KH550, 0.05 wt% of catalyst dibutyltin dilaurate, 65 wt% of DBU modified aluminum hydroxide filler prepared in step 1), 5 wt% of molecular sieve, and 0.95 wt% of hydrophobic silica were evacuated, stirred and mixed uniformly to obtain component A;
[0085] 5) Preparation of component B: 15 wt% of the isocyanate-terminated polyurethane prepolymer prepared in step 3), 12 wt% of liquefied MDI, 68 wt% of the pyruvic acid-modified aluminum hydroxide filler prepared in step 2), 0.6 wt% of a dehydrating agent, 0.9 wt% of hydrophobic silica, and 3.5 wt% of a plasticizer are evacuated and stirred to mix uniformly to obtain component B.
[0086] 6) The component A prepared in step 4) and the component B prepared in step 5) are mixed in a volume ratio of 1:1 to obtain a polyurethane thermal conductive structural adhesive.
[0087] Example 2
[0088] The present embodiment provides a polyurethane thermally conductive structural adhesive, which comprises component A and component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive is basically the same as that of Example 1, except that the pyruvic acid-modified aluminum hydroxide filler is replaced by a barbituric acid-modified aluminum hydroxide filler, wherein the preparation method of the barbituric acid-modified aluminum hydroxide filler is basically the same as the preparation method of the pyruvic acid-modified aluminum hydroxide filler, except that pyruvic acid is replaced by barbituric acid.
[0089] Example 3
[0090] The present embodiment provides a polyurethane thermally conductive structural adhesive, which comprises component A and component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive is basically the same as that of Example 1, except that the pyruvic acid-modified aluminum hydroxide filler is replaced by a lactic acid-modified aluminum hydroxide filler, wherein the preparation method of the lactic acid-modified aluminum hydroxide filler is basically the same as the preparation method of the pyruvic acid-modified aluminum hydroxide filler, except that pyruvic acid is replaced by lactic acid.
[0091] Example 4
[0092] The present embodiment provides a polyurethane thermally conductive structural adhesive, which includes component A and component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive is basically the same as that of Example 1, except that the pyruvic acid-modified aluminum hydroxide filler is replaced by an acetic acid-modified aluminum hydroxide filler, wherein the preparation method of the acetic acid-modified aluminum hydroxide filler is basically the same as the preparation method of the pyruvic acid-modified aluminum hydroxide filler, except that pyruvic acid is replaced by acetic acid.
[0093] Example 5
[0094] The present embodiment provides a polyurethane thermally conductive structural adhesive, which comprises component A and component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive is basically the same as that of Example 1, except that: the DBU-modified aluminum hydroxide filler is replaced with a triethylamine-modified aluminum hydroxide filler, wherein the preparation method of the triethylamine-modified aluminum hydroxide filler is basically the same as the preparation method of the DBU-modified aluminum hydroxide filler, except that DBU is replaced with triethylamine.
[0095] Example 6
[0096] The present embodiment provides a polyurethane thermally conductive structural adhesive, which comprises component A and component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive is basically the same as that of Example 1, except that the silane coupling agent used in the preparation of the DBU-modified aluminum hydroxide filler and the pyruvic acid-modified aluminum hydroxide filler is replaced by dodecyltriethoxysilane from octadecyltriethoxysilane.
[0097] Example 7
[0098] The present embodiment provides a polyurethane thermally conductive structural adhesive, which comprises component A and component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive is basically the same as that of Example 1, except that the silane coupling agent used in the preparation of the DBU-modified aluminum hydroxide filler and the pyruvic acid-modified aluminum hydroxide filler is replaced by hexadecyltriethoxysilane from octadecyltriethoxysilane.
[0099] Example 8
[0100] The present embodiment provides a polyurethane thermally conductive structural adhesive, which comprises a component A and a component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive is basically the same as that of Example 1, except that in the preparation of the terminal isocyanate polyurethane, dihydrochloride is replaced by methyl propylene glycol.
[0101] Example 9
[0102] The present embodiment provides a polyurethane thermally conductive structural adhesive, which comprises a component A and a component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive is basically the same as that of Example 1, except that in the preparation of the terminal isocyanate polyurethane, dihydrochloride is replaced by methyl pentanediol.
[0103] Example 10
[0104] The present embodiment provides a polyurethane thermally conductive structural adhesive, which comprises a component A and a component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive is basically the same as that of Example 1, except that, in the preparation of the terminal isocyanate polyurethane, the homemade polyester polyol derived from dichlorvos is replaced by the commercially available Jingri 3190 polyester polyol (molecular weight of 1900-2100Da, hydroxyl value of 53-59mgKOH / g).
[0105] Embodiment 11
[0106] This embodiment provides a polyurethane thermal conductive structural adhesive, which includes component A and component B in a volume ratio of 1:1. The preparation method of the thermal conductive structural adhesive is basically the same as that of Example 1, except that the preparation method of the isocyanate-terminated polyurethane prepolymer includes the following steps:
[0107] Adipic acid and chlorpyrifos were mixed at a mass ratio of 1000:1500 and added to a four-necked flask at room temperature, with nitrogen protection, condensed and refluxed. The mixture was heated from room temperature to 80°C to partially melt the material, and then stirred and heated to 145°C for esterification reaction, and kept warm for 8 hours. Subsequently, the temperature was raised to 230°C at a rate of 10°C / min to carry out a condensation reaction, the reaction was kept warm for 3.5 hours, phthalate accounting for 0.1% of the total mass of adipic acid and repellent alcohol was added, and the reaction was kept warm for 4 hours to obtain a polyester polyol derived from repellent alcohol with a molecular weight of 600-800Da and a hydroxyl value of 140-160mgKOH / g; 380g of the prepared polyester polyol derived from repellent alcohol was heated to 110°C, evacuated, stirred and dehydrated for 2 hours, cooled to 60-65°C, 600g of liquefied MDI was added, the temperature was raised to 80°C, the reaction was carried out for 2 hours, and then cooled to room temperature to prepare a terminal isocyanate-based polyurethane prepolymer.
[0108] Example 12
[0109] This embodiment provides a polyurethane thermal conductive structural adhesive, which includes component A and component B in a volume ratio of 1:1. The preparation method of the thermal conductive structural adhesive is basically the same as that of Example 1, except that the preparation method of the isocyanate-terminated polyurethane prepolymer includes the following steps:
[0110] Adipic acid and chlorpyrifos were mixed at a mass ratio of 1000:1300 and added to a four-necked flask at room temperature, with nitrogen protection, condensed and refluxed. The mixture was heated from room temperature to 80°C to partially melt the material, and then stirred and heated to 145°C for esterification reaction, and kept warm for 8 hours. Subsequently, the temperature was raised to 220°C at a rate of 10°C / min to carry out a condensation reaction, the reaction was kept warm for 2.5 hours, phthalate accounting for 0.1% of the total mass of adipic acid and repellent alcohol was added, and the reaction was kept warm for 4 hours to obtain a polyester polyol derived from repellent alcohol with a molecular weight of 1400-1600Da and a hydroxyl value of 70-80mgKOH / g; 500g of the prepared polyester polyol derived from repellent alcohol was heated to 110°C, evacuated, stirred and dehydrated for 2 hours, cooled to 60-65°C, 600g of liquefied MDI was added, the temperature was raised to 80°C, the reaction was carried out for 2 hours, and then cooled to room temperature to prepare a terminal isocyanate-based polyurethane prepolymer.
[0111] Comparative Example 1
[0112] This comparative example provides a polyurethane thermally conductive structural adhesive, which comprises a component A and a component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive is basically the same as that of Example 1, except that the pyruvic acid-modified aluminum hydroxide filler is replaced by an inorganic filler modified only with octadecyltriethoxysilane. The preparation method of the filler comprises the following steps:
[0113] Weigh the aluminum hydroxide raw material and put it in a beaker, add a mixed solvent of water and ethanol with a volume ratio of 1:1 to dissolve it, so that the system reaches a liquid-solid ratio of 1:1 by mass, and then weigh 3% octadecyl triethoxysilane and add it to the reaction system. At 80°C and a speed of 1000r / min, the modification is carried out for 40 minutes to complete the modification process. The modified product is filtered and placed in an electric heating blast drying oven for drying. After 8 hours, it is taken out to obtain a dry modified aluminum hydroxide filler.
[0114] Comparative Example 2
[0115] This comparative example provides a polyurethane thermally conductive structural adhesive, which comprises component A and component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive is basically the same as that of Example 1, except that the DBU-modified aluminum hydroxide filler is replaced by an inorganic filler modified with octadecyltriethoxysilane. The preparation method of the filler is the same as that of Comparative Example 1.
[0116] Comparative Example 3
[0117] This comparative example provides a polyurethane thermally conductive structural adhesive, which comprises a component A and a component B in a volume ratio of 1:1. The preparation method of the thermally conductive structural adhesive comprises the following steps:
[0118] 1) Preparation of component A: 17 wt% of castor oil, 9 wt% of ethoxylated bisphenol A modified polyester polyol, 2.5 wt% of 1,4-butanediol, 0.5 wt% of coupling agent KH550, 0.05 wt% of catalyst dibutyltin dilaurate, 64.92 wt% of aluminum hydroxide filler, 5 wt% of molecular sieve, 0.95 wt% of hydrophobic silica, and 0.08 wt% of DBU were vacuumed and stirred to mix evenly to obtain component A;
[0119] 2) Preparation of component B: 15 wt% of terminal isocyanate polyurethane prepolymer, 12 wt% of liquefied MDI, 67.92 wt% of aluminum hydroxide filler, 0.6 wt% of dehydrating agent, 0.9 wt% of hydrophobic silica, 3.5 wt% of plasticizer, and 0.08 wt% of pyruvic acid were vacuumed and stirred to mix uniformly to obtain component B;
[0120] The isocyanate-terminated polyurethane prepolymer was prepared by referring to the method of Example 1.
[0121] Test Case
[0122] The following properties of the polyurethane thermal conductive structural adhesives prepared in the above examples and comparative examples were tested:
[0123] A. Opening hours
[0124] Test method: Take 50g of component B and place it in a disposable cup, store it openly in a standard environment (25°C, 53% RH), and record the time when crystallization and crusting appear on its surface.
[0125] B. Thermal conductivity
[0126] Test method: Tested in accordance with ASTM D5470.
[0127] C. Shear strength
[0128] Test method: Test in accordance with GB / T 7124-2008. Shear strength can be used to characterize the bonding performance of polyurethane thermal conductive structural adhesive. The greater the shear strength, the better the bonding performance of the polyurethane thermal conductive structural adhesive.
[0129] D. Tensile strength
[0130] Test method: Test in accordance with GB / T 528-2009.
[0131] E. Elongation at break
[0132] Test method: Test in accordance with GB / T 528-2009.
[0133] F. Pull-out strength
[0134] Test method: Test in accordance with GB / T 7124-2008.
[0135] The test results of the above performance are shown in Table 1.
[0136] Table 1
[0137]
[0138] The following conclusions can be drawn from Table 1:
[0139] 1) From the comparison between Examples 1 to 5 and Comparative Examples 1, 2 and 3, it can be seen that when the inorganic filler surface-coated and modified by organic acid is not included in component A, the open time of component B of the polyurethane thermal conductive structural adhesive is significantly shortened on the basis of comparable properties such as thermal conductivity, shear strength, tensile strength, elongation at break, and pull-out strength; when the inorganic filler surface-coated and modified by organic base is not included in component B, although component B has a longer open time, the shear strength, tensile strength, elongation at break and pull-out strength of the polyurethane thermal conductive structural adhesive are significantly reduced; when the organic acid and the organic base are directly blended with the other components in component B and component A, instead of using the organic acid and the organic base to surface-coat and modify the inorganic fillers in component B and component A respectively, the uniformity of the organic acid in component B is poor, which makes it difficult to effectively extend the open time of component B, and the addition of the organic acid in component B will cause certain corrosion to the substrate, resulting in a significant decrease in the shear strength, tensile strength, elongation at break and pull-out strength of the polyurethane thermal conductive structural adhesive.
[0140] From the comparison of Examples 1 to 4, it can be seen that compared with acetic acid modification, the inorganic fillers modified by surface coating with pyruvic acid, lactic acid and barbituric acid have excellent thermal conductivity, shear strength, tensile strength, elongation at break, and pull-out strength, and their open time is significantly longer, among which the open time of the inorganic filler modified with pyruvic acid is the most advantageous;
[0141] From the comparison between Examples 1 and 5, it can be seen that compared with the triethylamine modification, the shear strength, tensile strength, elongation at break and pull-out strength of the inorganic filler modified with DBU are more advantageous.
[0142] 2) From the comparison of Examples 1, 6, and 7, it can be seen that the silane coupling agent used in the modification process of the inorganic filler also has a certain influence on the open time and the strength properties of the structural adhesive. Among them, the structural adhesive obtained by using octadecyltriethoxysilane as a coupling agent to participate in the modification has the best open time and strength properties.
[0143] 3) From the comparison of Examples 1, 8, 9, and 10, it can be seen that the type of polyester polyol used in the preparation process of the terminal isocyanate polyurethane prepolymer has a significant effect on the open time. Among them, the terminal isocyanate polyurethane prepolymer prepared from the polyester polyol derived from the mosquito repellent alcohol can be applied to the B component to significantly extend the open time of the B component. This is because the carbon side chains in the mosquito repellent alcohol can be coated on the surface of the prepolymer to form an additional hydrophobic layer. The second is the polyester polyol prepared from methyl pentanediol and methyl propylene glycol, respectively. This is because the hydrophobic type of methyl pentanediol is better than that of methyl propylene glycol, but the molecular chain is shorter, and the coating hydrophobic effect is weaker than that of the mosquito repellent alcohol. The terminal isocyanate polyurethane prepolymer prepared from the 3190 polyester polyol has the shortest open time when applied to the B component.
[0144] 4) From the comparison of Examples 1, 11, and 12, it can be seen that the hydroxyl value and molecular weight of the polyester polyol used in the preparation process of the terminal isocyanate polyurethane prepolymer also have a certain influence on the open time. Among them, when the molecular weight of the polyester polyol is 2800-3200Da and the hydroxyl value is 34-40mgKOH / g, the open time of component B is the longest. The larger the molecular weight, the longer the molecular chain of the polyester polyol. The longer molecular chain is conducive to improving the hydrophobic property, and within the range of the molecular weight and hydroxyl value, it can inhibit its reaction with moisture in the air, thereby further extending the open time of component B.
[0145] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A polyurethane thermal conductive structural adhesive, characterized in that: It includes component A and component B in a volume ratio of (0.9~1.1):1; The component A comprises, by weight percentage, 15 wt% to 35 wt% of castor oil, 5 wt% to 14 wt% of the first polyester polyol, 2 wt% to 5 wt% of a chain extender, 0.5 wt% to 2.5 wt% of a coupling agent, 0.02 wt% to 0.08 wt% of a catalyst, 50 wt% to 70 wt% of a first modified inorganic filler, 5 wt% to 8 wt% of a molecular sieve, and 0.5 wt% to 2.5 wt% of hydrophobic silica; The B component includes, by weight percentage: 5wt% to 15wt% of terminal isocyanate polyurethane prepolymer, 5wt% to 15wt% of isocyanate, 50wt% to 70wt% of second modified inorganic filler, 0.5wt% to 2.5wt% of water remover, 0.3wt% to 1.5wt% of hydrophobic silica, and 0 to 3.5wt% of plasticizer; The first modified inorganic filler includes a first inorganic filler and a first modified layer coated on the surface of the first inorganic filler, and the first modified layer includes an organic base; The second modified inorganic filler includes a second inorganic filler and a second modified layer coated on the surface of the second inorganic filler, and the second modified layer includes an organic acid; The isocyanate-terminated polyurethane prepolymer is obtained by reacting a second polyester polyol and an isocyanate in a mass ratio of (20-50): (50-80); The second polyester polyol is obtained by polymerizing a diol and a dicarboxylic acid; the molecular weight of the second polyester polyol is 500-3500 Da, and the hydroxyl value is 30-224 mgKOH / g; The diol is selected from branched diols, including one or more of methyl propylene glycol, methyl pentanediol, and dihydrochloric acid; The organic acid is selected from one or more of pyruvic acid, barbituric acid, and lactic acid; The organic base is selected from 1,8-diazabicycloundec-7-ene; The first inorganic filler and the second inorganic filler are each independently selected from one or more of aluminum oxide, aluminum hydroxide, and magnesium oxide.
2. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The diol is dihydrochloric acid alcohol, the molecular weight of the second polyester polyol is 2800-3200Da, and the hydroxyl value is 32-40 mgKOH / g.
3. The polyurethane thermal conductive structural adhesive according to claim 1 or 2, characterized in that: The organic acid has a pKa value of 2 to 5, a boiling point of >100°C, and a solubility of >0.1 g / 100 g water; And / or, the organic base has a pKb value of 0.5-4 and a solubility of >0.1 g / 100 g water.
4. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The first modified inorganic filler is prepared by a method comprising the following steps: dispersing the first inorganic filler in deionized water, adding the organic base thereto to obtain a first dispersion with a solid content of 40% to 60%, adding a first silane coupling agent to the first dispersion, reacting at 60 to 80° C. for 30 min to 60 min to obtain the first modified inorganic filler; the amount of the organic base added is 100 to 1000 ppm of the mass of the deionized water in the first dispersion; And / or, the second modified inorganic filler is prepared by a method comprising the following steps: dispersing the second inorganic filler in deionized water, adding the organic acid thereto to obtain a second dispersion with a solid content of 40% to 60%, adding a second silane coupling agent to the second dispersion, reacting at 60 to 80° C. for 30 min to 60 min to obtain the second modified inorganic filler; the amount of the organic acid added is 0.1 to 10 ppm of the mass of the deionized water in the second dispersion.
5. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The amount of the organic base added is 200-500 ppm, and the amount of the organic acid added is 0.5-2.5 ppm.
6. The polyurethane thermal conductive structural adhesive according to claim 4, characterized in that: The first silane coupling agent and the second silane coupling agent are independently selected from one or more of dodecyltriethoxysilane, octadecyltriethoxysilane coupling agent, and hexadecyltriethoxysilane coupling agent.
7. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The chain extender is selected from one or more of dipropylene glycol, diethylene glycol, and 1,2-propylene glycol; And / or, the dewatering agent is selected from one or more of toluenesulfonyl isocyanate and triethyl orthoformate; And / or, the isocyanate is selected from one or more of 4,4'-dicyclohexylmethane diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, polymethylene polyphenyl polyisocyanate; And / or, the catalyst is selected from one or more of aliphatic amine catalysts and organic metal catalysts.
Citation Information
Patent Citations
Bi-component polyurethane heat-conducting structural adhesive and preparation method thereof
CN113736419A
High-temperature-resistant heat-conducting polyurethane structural adhesive and preparation method thereof
CN115785887A